Peningkatan Edukasi Dan Literasi Gizi Guna Mengatur Pola Makan Anak Pada Masa Pandemi Di Desa Jatisari Kabupaten Boyolali - Fatimah Ibtisam; Ahmad Farhan Baihaqqi; Alifia Divana Ayu Swastikaningrum; Ayu Rohani; Firnadia Septika Rahajeng; Indar Hidayat; Nadhira Ahadea Noorsy; Regita Aulia Sari; Shella Novitasari; Septi Khairunisa; Rezania Asyfiradayati (Masokan: Ilmu Sosial dan Pendidikan, 2021)
Background: The situation of the Covid-19 outbreak that continues to increase has prompted the government to issue policies in an effort to break the chain of spread of the Covid-19 virus. One way to increase public awareness is by providing education about the importance of maintaining a balanced diet during the pandemic.  Objective: To increase children's knowledge, especially in Jatisari Village about the importance of maintaining a diet during the Covid-19 pandemic. Method: This study uses a qualitative descriptive method, namely collecting data on the independent variable and the dependent variable at one time. Results: what was obtained after the presentation of the material was an increase in children's knowledge and awareness of the importance of maintaining a balanced diet during a pandemic. This can be measured by the enthusiasm of the participants in answering questions and their activeness in carrying out the practice. Target: This program is for children under 15 years old and over 7 years old. Latar belakang: Keadaan wabah Covid-19 yang terus meningkat membuat pemerintah mengeluarkan kebijakan sebagai upaya memutuskan mata rantai penyebaran virus Covid-19.  Salah satu cara untuk meningkatkan kesadaran masyarakat yaitu dengan memberikan edukasi mengenai pentingnya menjaga pola makan seimbang dimasa pandemi. Tujuan: Meningkatkan pengetahuan anak khususnya di Desa Jatisari akan pentingnya menjaga pola makan di masa pandemi Covid-19. Metode: penelitian ini menggunakan metode deskriptif kualitatif yaitu mengumpulkan data mengenai variable bebas dan variable terikat dalam satu waktu. Hasil: yang didapatkan setelah pemaparan materi adalah peningkatan pengetahuan dan kesadaran anak akan pentingnya menjaga pola makan seimbang di kala pandem.  Hal ini dapat diukur dari antusiasme peserta dalam menjawab pertanyaan dan keaktifan dalam melakukan praktik. Sasaran: Program ini adalah untuk anak-anak dibawah usia 15 tahun dan di atas usia 7 tahun.